Erratum: Mayevskaya M.V. et al., “An Effect of Ursodeoxycholic Acid on Inflammation, Steatosis and Liver Fibrosis and Atherogenesis Factors in Patients with Non-Alcoholic Fatty Liver Disease: Results of the USPEH Study” - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.